2018
DOI: 10.1063/1.5030068
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically confined electron beam system for high resolution electron transmission-beam experiments

Abstract: A novel experimental setup has been implemented to provide accurate electron scattering cross sections from molecules at low and intermediate impact energies (1-300 eV) by measuring the attenuation of a magnetically confined linear electron beam from a molecular target. High-resolution electron energy is achieved through confinement in a magnetic gas trap where electrons are cooled by successive collisions with N. Additionally, we developed and present a method to correct systematic errors arising from energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(89 citation statements)
references
References 20 publications
5
84
0
Order By: Relevance
“…1 are the TCS results from the previous measurements of Wan et al 14 and Karwasz et al, 15 along with theoretical IAM-SCAR+I and IAM-SCAR+I+rotations total cross sections of Krupa et al 12 and an SCOP result of 15 (green crosses) and theoretical IAM-SCAR+I (blue solid curve) 12 and IAM-SCAR+I+rotations (blue short dashed curve) 12 and SCOP (brown dotted curve) 16 results. The IAM-SCAR+I+rotations result when corrected for the "missing angle" effect (black dotted-dashed curve) 19 and the measured elastic ICSs of Hlousek et al 13 (red open circles) are also shown. Note that the uncertainties on the present data are statistical only.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 are the TCS results from the previous measurements of Wan et al 14 and Karwasz et al, 15 along with theoretical IAM-SCAR+I and IAM-SCAR+I+rotations total cross sections of Krupa et al 12 and an SCOP result of 15 (green crosses) and theoretical IAM-SCAR+I (blue solid curve) 12 and IAM-SCAR+I+rotations (blue short dashed curve) 12 and SCOP (brown dotted curve) 16 results. The IAM-SCAR+I+rotations result when corrected for the "missing angle" effect (black dotted-dashed curve) 19 and the measured elastic ICSs of Hlousek et al 13 (red open circles) are also shown. Note that the uncertainties on the present data are statistical only.…”
Section: Resultsmentioning
confidence: 99%
“…Other random uncertainties are related to the temperature measurement (∼1% according to the manufacturer's data) and the numerical fitting procedure (∼1%) associated with the analysis of the RPA cut-off curves. 19 By combining these uncertainties, a total error limit of ±6% has been determined for the present TCSs. Systematic errors linked to the experimental configuration are those connected to the so-called "missing angles."…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations